Teacher-Researchers Celebrating Peer Influences: Collaboration and Challenge - Myriam N. Torres (Networks: An Online Journal for Teacher Research, 1999)
Introduction: Isolation is a frequently emergent issue in teachers' conversations about their experiences and concerns. Through these collegial conversations, teachers discover the power of collaboration for their own development and that of their students. The celebration of this discovery is described and documented in this paper by examining their discourse as they talk and write about their experiences in doing teacher research in a collaborative atmosphere. Using Sampson's (1993) poetic expression, teachers were "Celebrating the other".